Los comentarios del inca y la leyenda del Perú - Coello, Óscar (2021)
This article seeks to connect the original legend of Peru with the artistic narration of the Inca’s country that Garcilaso proposes in the Royal Comments. After recalling the legend of Peru at the beginnings of the 16th century, it explains about some fabulous narrations which were already part of the imaginary of the America discoverers. Furthermore, it describes the emergence of the hybrid, Spanish and Indian legends, which appeared after Cajamarca’s capture.